Roles of FGF20 in dopaminergic neurons and Parkinson's disease - Itoh, Nobuyuki; Ohta, Hiroya (Frontiers in Molecular Neuroscience, 2013)
The fibroblast growth factor (FGF) family comprises 22 members with diverse functions in development and metabolism. Fgf20 was originally identified as a new Fgf preferentially expressed in the substantia nigra pars compacta. Fgf20, which acts on proximal cells, significantly enhanced the survival of cultured dopaminergic neurons by activating the MAPK pathway through Fgf receptor 1c. In the rat model of Parkinson's disease, Fgf20 afforded significant protection against the loss of dopaminergic neurons. The significant correlation of Parkinson’s disease with single-nucleotide polymorphisms in FGF20 indicates that the genetic variability of FGF20 can be a Parkinson’s disease risk. Neural and embryonic stem cells have been considered as cell resources for restorative transplantation strategies in Parkinson's disease. Fgf20 promoted the differentiation of these stem cells into dopaminergic neurons, which attenuated neurological symptoms in animal models of Parkinson's disease. These findings indicate the importance of FGF20 for the differentiation and survival of dopaminergic neurons and the etiology and therapy of Parkinson’s disease.